Предмет: Алгебра,
автор: diana67955
(х-5)(2х+3)-(х+4)(4-х)=2х+5
Ответы
Автор ответа:
0
2х^2+3х-10х-15-х^2-16=2х+5
2х^2+3х-10х-15-2х^2-16-2х-5=0
-5х-36=0
-5х=36
х=36/(-5)
х=-7,2
ответ 7,2
2х^2+3х-10х-15-2х^2-16-2х-5=0
-5х-36=0
-5х=36
х=36/(-5)
х=-7,2
ответ 7,2
Автор ответа:
0
вы уверены что это правильно?
Похожие вопросы
Предмет: Математика,
автор: radchenkokira8
Предмет: География,
автор: likkkluxr
Предмет: Физика,
автор: Mashka7002
Предмет: Биология,
автор: Аноним
Предмет: Алгебра,
автор: rayps